ANALISIS KEJADIAN STRESS ULCER PADA PASIEN STROKE SEBAGAI PREDIKTOR ANGKA MORTALITAS - Tjondronegoro, Astuti; Nur Azizah, Aji Muthiah; Claudia, Vemmy Octaviana (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Stroke is a life-threatening disease with high incidence and mortality rates, causing significant disability. WHO predicts that deaths due to stroke will increase to 8 million in 2030. Stroke can also cause damage to peripheral organs, one of which is stress ulcers. These complications can affect treatment and prognosis and are associated with increased mortality. Aim: This study aims to determine the relationship between the incidence of stress ulcers and mortality rates in stroke patients. Methods: This research used a retrospective observational approach. Data was obtained through medical records of patients diagnosed with stroke at Prambanan Hospital Inpatient Installation from January 2022 to December 2022. Characteristics assessment of stroke patients used univariate analysis, while stress ulcer incidence with patient mortality rates used bivariate analysis (Pearson Chi-Square and coefficient contingency). Results: In this study, male patients (50.7%) and those over 60 (67.9%) had the highest stroke rates. The incidence of stress ulcers in stroke patients was 22 people (15.7%), and 32 stroke patients were declared dead (22.9%). Bivariate analysis showed that stress ulcers in stroke patients were a strong risk factor for mortality (OR=12.731, 95% CI=4.528-35.799, p < 0.001). Discussion: Risk factors for stroke are age, gender, history of disease (hypertension, cardiovascular, dyslipidemia, diabetes mellitus), and smoking. Hemorrhagic strokes have more potential to cause stress ulcers than ischemic strokes. Stress ulcers resulting from chronic stress response from HPA-axis dysregulation strongly predict mortality rates for stroke patients in the Prambanan Hospital Inpatient Installation. Keywords: Mortality, stress ulcer, stroke